Nuclear magnetic resonance analysis of emulsified silicone oil RMN-3 (Oxane HD). Issue 10 (12th April 2007) - Tomlins, Paul J; Woodcock, Malcolm G L; Spencer, Neil; Kirkby, Graham R
Abstract : Background: Oxane HD is a mixture of 5700 cs silicone oil and RMN-3 (a partly fluorinated olefin), which has a specific gravity greater than water, thereby enabling endotamponade of inferior retinal breaks. Droplets of emulsified oil were found in the anterior chamber of two patients with complex retinal detachments who had been treated with Oxane HD. Samples removed from these two eyes were analysed in order to investigate the nature of the emulsified substance. Methods: Samples were dissolved in CDCl3 and, if necessary, dried using magnesium sulphate. Nuclear magnetic resonance (NMR) was used to compare these samples with the unused commercial product. Results: NMR analysis of the samples removed from the anterior segment of both eyes were mainly silicone oil with only trace amounts of RMN-3. Samples taken from different areas of an unused syringe of Oxane HD demonstrated varying concentrations of the RMN-3 compound within the silicone oil. Conclusion: First, the mixture of RMN-3 and silicone oil is not homogenous either in vitro or in vivo . Second, emulsified oil found in the anterior chamber is composed almost entirely of silicone oil, containing only trace amounts of RMN-3.